Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1186/gm144
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of post-transcriptional gene regulatory networks associated with autism spectrum disorders by microRNA expression profiling of lymphoblastoid cell lines

Abstract: BackgroundAutism spectrum disorders (ASD) are neurodevelopmental disorders characterized by abnormalities in reciprocal social interactions and language development and/or usage, and by restricted interests and repetitive behaviors. Differential gene expression of neurologically relevant genes in lymphoblastoid cell lines from monozygotic twins discordant in diagnosis or severity of autism suggested that epigenetic factors such as DNA methylation or microRNAs (miRNAs) may be involved in ASD.MethodsGlobal miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
191
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(199 citation statements)
references
References 215 publications
2
191
1
5
Order By: Relevance
“…Sarachana et al. reported downregulation of miR‐219‐5p and miR‐133b in lymphoblast cell lines from ASD patients 8. In particular, they confirmed that miR‐219‐5p targeted Polo like kinase 2 ( PLK2 ), whose activation in neurons is dependent on synaptic activity and is involved in homeostatic regulation of synaptic plasticity 41.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Sarachana et al. reported downregulation of miR‐219‐5p and miR‐133b in lymphoblast cell lines from ASD patients 8. In particular, they confirmed that miR‐219‐5p targeted Polo like kinase 2 ( PLK2 ), whose activation in neurons is dependent on synaptic activity and is involved in homeostatic regulation of synaptic plasticity 41.…”
Section: Discussionmentioning
confidence: 81%
“…reported conflicting results; prenatal exposure to valproic acid upregulated miR‐132‐5p expression in the embryonic mouse brain 33. However, the effect of miR‐132‐5p upregulation was transient, lasting only 18–24 h after valproic acid exposure, which might explain the opposite direction of miR‐132‐5p dysregulation, compared to other studies in human cases 8, 9…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Until now, studies have centered more on genetic factors, but only a few studies have investigated the role of miRNA as epigenetic factors involved in ASD. [2][3][4] Epigenetic factors regulate heritable modifi cations in gene function or activity without changes of the DNA sequence. МicroRNAs have recently became leading epigenetic regulators of various cellular processes.…”
mentioning
confidence: 99%
“…These mechanisms are implicated in cognition, eating disorders, depression, autism and schizophrenia (25,(31)(32)(33) . Studies on other epigenetic mechanisms involving RNA methylation, non-coding microRNA, telomere control and chromosomal position effects should also provide new understanding of mechanisms linking nutrition and brain health (23,34,35) .…”
Section: Nutrition and Gene Expression: Epigeneticsmentioning
confidence: 99%